2016
DOI: 10.1515/jtim-2016-0030
|View full text |Cite
|
Sign up to set email alerts
|

Association of serum intact fibroblast growth factor 23 with left ventricular mass and different echocardiographic findings in patients on hemodialysis

Abstract: Objectives: To determine the association of fibroblast growth factor 23 (FGF23) with left ventricular hypertrophy (LVH) through the assessment of left ventricular (LV) mass and left ventricular mass index (LVMI) in patients on hemodialysis, this study was done. Methods: All patients on hemodialysis who are older than 18 years and in whom hemodialysis vintage was at least 6 months were enrolled. All patients were on hemodialysis thrice a week for 4 h using low-flux dialysis filters, polysulfone membranes, rever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
1
2
0
Order By: Relevance
“…Moreover, the role of sKlotho in the development of atherosclerotic disease in dialysis patients might be overshadowed by a large amount of other pathophysiological stimuli for CVD prevalent in these patients, such as smoking, obesity, diabetes and hypertension among others (11). As reported by previous studies, our study also reported an association between FGF-23 and LV mass index (13)(14)(15). A majority of our patients had a high left ventricular mass index (mean: 122.5 ± 22.74 g/m 2 ), compared to previously established references for healthy men and women, which is not surprising in view of their CKD and elevated FGF-23 levels (16,17).…”
Section: Discussionsupporting
confidence: 78%
“…Moreover, the role of sKlotho in the development of atherosclerotic disease in dialysis patients might be overshadowed by a large amount of other pathophysiological stimuli for CVD prevalent in these patients, such as smoking, obesity, diabetes and hypertension among others (11). As reported by previous studies, our study also reported an association between FGF-23 and LV mass index (13)(14)(15). A majority of our patients had a high left ventricular mass index (mean: 122.5 ± 22.74 g/m 2 ), compared to previously established references for healthy men and women, which is not surprising in view of their CKD and elevated FGF-23 levels (16,17).…”
Section: Discussionsupporting
confidence: 78%
“…In addition, FGF23 has direct cardiac and vascular poisonous [24,25], independent on α-klotho. Several clinical researches have confirmed that FGF23 had an association with left ventricular mass, ejection fraction, left ventricular end-diastolic dimension, and vascular calcification [26,27]. These factors are associated with an adverse outcome in health individuals and hemodialysis patients.…”
Section: Discussionmentioning
confidence: 94%
“…The relationship between FGF23 and the development of LVH in CKD patients has been described [ 44 ], but contradictory data has been reported in dialysis patients. Some studies described an association between FGF23 and LVH in dialysis patients [ 73 ] while others authors did not find associations between serum FGF23 levels and LVH [ 74 , 75 ]. Thus, the QT interval prolongation observed in our cohort might indeed be due to the increased levels of FGF23 in the dialysis patients, which is also experimentally supported by the increased QT interval duration observed in healthy mice after a single FGF23 injection.…”
Section: Discussionmentioning
confidence: 99%